ChemInform Abstract: Synthesis, Characterization and Electrochemical Performance of Li2FeSiO4/C for Lithium‐Ion Batteries. Issue 17 (4th April 2013) - Chen, Weihua; Lan, Meng; Zhu, Dan; Wang, Cuilian; Xue, Shangru; Yang, Changchun; Li, Zexian; Zhang, Jianmin; Mi, Liwei
Abstract Li2FeSiO4/C is synthesized by solid state reaction of Li2SiO3 (obtained by ball milling of LiOH·H2O and H2SiO3), FeC2O4, citric acid, and sucrose (923 K, 7 h).